Pendidikan Keluarga Profetik untuk Meningkatkan Kreativitas Anak - Rahmat, Asep (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2020)
The background of the phenomenon is that teenagers are involved in various mal-adaptive behaviors, including juvenile delinquency, involved in drugs, free sex, addiction to games, truancy, lazy to do assignments and tend to be a generation of 'lay down' and ultimately do not have creativity in their lives. This article aims to describe prophetic-based family education in order to increase children's creativity in their lives. The method used in this article uses a literature review by searching for keyword entries in several journal engines and several e-book sources and some relevant classic literature. The results of the literature review in this article can be used as a comprehensive reference for research development for family prophetic education to increase children's creativity. Keywords: family education; prophetic, children's creativity